Las relaciones interpersonales de los docentes de la escuela “Mariscal Sucre” con la comunidad educativa en la pandemia del Covid-19. - Hurtado, Betty V. (2022)
Interpersonal relationships are very important within the school work field because through them a harmonious coexistence within the school is generated or not; for this reason, the teacher must maintain a good climate in the classroom and in the school, for which he/she must develop a series of skills to relate, communicate, and resolve conflicts with other members of the educational community. During the COVID-19 pandemic, school activities changed from face-to-face to virtual, which undoubtedly changed the way of interrelating, a situation that has generated other types of disagreements, confrontations and conflicts between teachers, students, authorities and parents; for this reason, the main objective of the study is to determine the situation of interpersonal relationships of teachers at the "Mariscal Sucre" school with the aforementioned groups. The approach of the study was quantitative, its level was descriptive, non-experimental, and the study was field and cross-sectional. To obtain information on the problem of teachers' interpersonal relationships, the survey technique was used, and four questionnaires of 8 questions were applied to teachers and 9 to students, directors and parents; these instruments were validated with Cronbach's Alpha and applied online. The results determine those personal relationships, communication and the level of conflicts of teachers during the pandemic were affected positively and in others negatively when relating with students, their representatives, fellow teachers and authorities.